2022
DOI: 10.1111/apa.16472
|View full text |Cite
|
Sign up to set email alerts
|

Association of platelet deficiency with severe retinopathy of prematurity: a review

Abstract: Aim The aim of this review was to compile existing evidence on the role of platelets in the development of severe retinopathy of prematurity (ROP), highlight the strengths and weaknesses of the available studies and critically discuss the reported data. Methods A comprehensive literature search was conducted on PubMed from January 2000 to January 2022, and the reference lists of the included studies were screened manually. Results There were 19 primary studies that fulfilled the eligibility criteria. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
(228 reference statements)
1
7
1
Order By: Relevance
“…Our study showed no significance between platelet count and the development of ROP in either eye. This goes against a review by Seliniotaki et al, which concluded that platelet deficiency was associated with severe forms of ROP [26]. This conflict in results between our study and others in the literature might be due to the fact that the majority of thrombocytopenic neonates who were included in our study had mild platelet deficiency.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed no significance between platelet count and the development of ROP in either eye. This goes against a review by Seliniotaki et al, which concluded that platelet deficiency was associated with severe forms of ROP [26]. This conflict in results between our study and others in the literature might be due to the fact that the majority of thrombocytopenic neonates who were included in our study had mild platelet deficiency.…”
Section: Discussioncontrasting
confidence: 99%
“…In the same study, retinal VEGF-A expression was found to be induced with platelet depletion and decreased with platelet transfusion and that clinically, platelet deficiency is associated with severe ROP ( Cakir et al, 2018 ). Other studies have also shown this association ( Jensen et al, 2018 ; Parrozzani et al, 2021 ; Şahinoğlu Keşkek et al, 2020 ; Seliniotaki et al, 2022 ). A hospital based prospective study found that platelet transfusion protects against ROP development ( Faheem et al, 2021 ).…”
Section: Introductionsupporting
confidence: 55%
“…In a retrospective case–control study, (Korkmaz et al, 2018) no differences in median PLT during ROP phase 1 (first 10 days of life) or ROP phase 2 (PMA ≥ 32 weeks for infants with GA < 27 weeks, PMA ≥ 33 weeks for infants with GA 27–29 weeks, PMA ≥ 34 weeks for infants with GA > 30 weeks) were found between cases and controls, while higher median PMI was ascertained in cases compared with controls during ROP phase 2, as opposed to our study. However, the above definitions of ROP phases are not widely accepted, and it is not clarified whether single PLT/PMI measurements or averaged values of multiple measurements were analysed (Hellström et al, 2013; Seliniotaki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These parameters could be included into a prognostic model for increasing the specificity of the applied ROP screening criteria. However, existing studies assessing platelet parameters present significant clinical heterogeneity and methodological limitations (Seliniotaki et al, 2022). Furthermore, prediction models incorporating postnatal weight gain, as a surrogate measure of IGF‐1, have been developed in high‐income countries and cannot be extrapolated to other populations without further validation (Athikarisamy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%